A study of piano teachers’ perception on the eclectic approach in elementary piano teaching / Khoo Chun Yong - Khoo , Chun Yong (2021)
Elementary piano teaching considers as a daunting task for piano teachers as the piano teacher needs to advocate a more holistic and student-centred approach to maximize the students’ music learning with numerous teaching techniques, strategies, and activities in a one-to-one teaching setting. The purpose of this study was to examine the piano teacher’s teaching approaches, selection of teaching materials, and their teaching activities in one-to-one elementary piano teaching. The participants of this study were nine piano teachers with different teaching experiences from West Malaysia. This study employed virtual interview which utilizing ICT (Information and Communicat ions Technology) medium or Internet-based communication tools like WhatsApp, Messenger, and e-mail. The findings of this study indicated that teachers were selecting and combining different teaching approaches, teaching materials, and teaching activities with their perspectives and teaching experiences to enhance piano learning and satisfy the needs of elementary piano students. They have applied an eclectic approach inadvertent ly in their elementary piano teaching as they choose and applied suitable teaching approaches, teaching materials, and teaching activities based on students’ needs. The implications of this study suggest that an eclectic approach applicable in piano education. The eclectic approach was based on the choice of piano teacher’s teaching approach with their evaluation on the readiness of student and the selection of suitable teaching materials to enhance the piano learning and performing of the student to the professional level. The eclectic approach can be an effective piano teaching approach to facilitate student’s piano learning and the acquiring of piano performance skills and techniques.